Քերականական համանունության դրսևորումները հայերենի բարբառների եղանակաժամանակային համակարգում - Գայանե Գևորգյան (ՀՀ ԳԱԱ հրատ.)
In the tense-aspect system of Armenian dialects there are intra-and interparadigmatic types of grammatical homonymy with their various manifestations. Interparadigmatic homonymy is expressed in the forms of finite-verbs, verbals and finite verbs, and infinite verbs conditioned by the homonymy of person-number forms and (word)-final units.
Keywords: Philology; Linguistics; Language and Literature